Evaluation of Control Monitoring Results in Drinking Water from Aspect of Public Health in Malatya Province (Annals of Medical Research, 2021)
Aim: Water sanitation is an essential practice to prevent diarrheal diseases. The aim of this study is to evaluate the results of monitoring of drinking water obtained in Malatya province.
Keywords: Drinking Water; Check Monitoring; Public Health.